Being differently the same: the mediation of identity tensions in the sharing of illness experiences. - Mazanderani, F; Locock, L; Powell, J (2012)
The sharing of experiences between patients has become increasingly privileged as a source of knowledge and support in contemporary healthcare. Despite this, relatively little is known about the processes whereby people's experiences become, or fail to become, valued as sources of health-related knowledge in different contexts. Through a secondary analysis of 87 interviews conducted between 2006 and 2008 in the UK with people affected by motor neurone disease (46 interviews) and Parkinson's disease (41 interviews), we explore the identity work involved in turning other people's experiences into 'experiential knowledge' that can be shared between patients. Of particular interest is how the turning of others' experiences into knowledge is presupposed by negotiating a particular type of identity tension - what, drawing on the work of Paul Ricoeur (2003) on metaphor, we refer to as 'being differently the same'. We examine the way in which people living with motor neurone disease and Parkinson's disease spoke of managing this tension as part of the process of accessing and valuing other patients' experiences, both epistemologically and emotionally. Instead of treating others' experiences as a pre-given source of knowledge, we emphasise how experience comes to be embodied and articulated through different media - bodies, speech, text, and images. Moreover, we suggest that paying closer attention to these media provides opportunities for enhancing our understanding of how people with different chronic and/or terminal illnesses use or do not use different forms of peer support - and in particular online ones - as a source of health-related experiential knowledge. Some of the implications of this are discussed in the specific context of people diagnosed with incurable neurodegenerative conditions characterised by visible physical deterioration and associated emotional distress.